(De facto) Legalization of abortion in Colombia - Gómez Rubio, Juan David (Derecho Público Iberoamericano, 2015)
The impossibility of legalizing abortion in Colombia by means of issuing laws produced a change in the stretegy of the population control advocates, which led, through strategic litigation, to a series of rulings that interpreted the Constitution according to the ideology of eugenics that underlies the birth control movement, de facto legalizing abortion on demand.